4+3t-4t=3(t-2)

Simple and best practice solution for 4+3t-4t=3(t-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+3t-4t=3(t-2) equation:


Simplifying
4 + 3t + -4t = 3(t + -2)

Combine like terms: 3t + -4t = -1t
4 + -1t = 3(t + -2)

Reorder the terms:
4 + -1t = 3(-2 + t)
4 + -1t = (-2 * 3 + t * 3)
4 + -1t = (-6 + 3t)

Solving
4 + -1t = -6 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.
4 + -1t + -3t = -6 + 3t + -3t

Combine like terms: -1t + -3t = -4t
4 + -4t = -6 + 3t + -3t

Combine like terms: 3t + -3t = 0
4 + -4t = -6 + 0
4 + -4t = -6

Add '-4' to each side of the equation.
4 + -4 + -4t = -6 + -4

Combine like terms: 4 + -4 = 0
0 + -4t = -6 + -4
-4t = -6 + -4

Combine like terms: -6 + -4 = -10
-4t = -10

Divide each side by '-4'.
t = 2.5

Simplifying
t = 2.5

See similar equations:

| x+4=3X-8+6X | | 7x^2-34x+24=0 | | 7x^2-34+24=0 | | 2d^2+14d-240=0 | | 3Y-27=9X | | 3x^4+2x^2-1=0 | | 4s^2+17s+15=0 | | 4(-6x-3y)=96 | | x^3+6x^2-32=0 | | 7(22-9x)=21y-161 | | 2x-3=4x+2 | | 5y-10y+13y= | | 0=23x-5+21x+5 | | 770=150+3100r | | 3x=6y+12 | | 0=x^3-2x^2-11x | | 0=-1+14x+12x+17 | | 132=x+139 | | 75=11x-2 | | x^2+4x+-77=0 | | 22x^2+41x+12=0 | | 22x^2+25x-12=0 | | 21x^2+55x+36=0 | | 4a^2+8a-21=0 | | 21x^2-x-36=0 | | 21x^2+x-36=0 | | 4b^2+21b+5=0 | | 6x-4=8x+5 | | -9t^2-5t+5t^3-t^3+12t^2-3t= | | 3(x^2+5-36)=0 | | 0.30(x-100000.00)=1000000 | | h^2+8h-84=0 |

Equations solver categories